Inducing the Alternative Oxidase Forms Part of the Molecular Strategy of Anoxic Survival in Freshwater Bivalves - Yusseppone, Maria S.; Rocchetta, Iara; Sabatini, Sebastian E.; Luquet, Carlos M.; Ríos de Molina, Maria del Carmen; Held, Christoph; Abele, Doris (Frontiers in Physiology, 2018)
Hypoxia in freshwater ecosystems is spreading as a consequence of global change, including pollution and eutrophication. In the Patagonian Andes, a decline in precipitation causes reduced lake water volumes and stagnant conditions that limit oxygen transport and exacerbate hypoxia below the upper mixed layer. We analyzed the molecular and biochemical response of the North Patagonian bivalve Diplodon chilensis after 10 days of experimental anoxia (< 0.2 mg O2 / L), hypoxia (2 mg O2 / L), and normoxia (9 mg O2 / L). Specifically, we investigated the expression of an alternative oxidase (AOX) pathway assumed to shortcut the regular mitochondrial electron transport system (ETS) during metabolic rate depression in hypoxia-tolerant invertebrates. Whereas the AOX system was strongly upregulated during anoxia in gills, ETS activities and energy mobilization decreased (less transcription of glycogen phosphorylase and succinate dehydrogenase in gills and mantle). Accumulation of succinate and induction of malate dehydrogenase (MDH) activity could indicate activation of anaerobic mitochondrial pathways to support anoxic survival in D. chilensis. Oxidative stress (protein carbonylation, glutathione peroxidase expression) and apoptotic intensity (caspase 3/7 activity) decreased, whereas an unfolded protein response (HSP90) was induced under anoxia. This is the first clear evidence of the concerted regulation of the AOX and ETS genes in a hypoxia-tolerant freshwater bivalve and yet another example that exposition to hypoxia and anoxia is not necessarily accompanied by oxidative stress in hypoxia-tolerant mollusks.